RETRACTED: The Effect of Training, Compensation and Work Discipline on Employee Performance at PT. Pegadaian - Ayu Lian Putri; Ahmad Cik; Kumba Digdowiseiso (Journal of Social Science, 2024)
This study aims to analyze the positive and significant effect of Training, Compensation and Work Discipline on Employee Performance. The research methodology used is quantitative method and uses multiple linear regression analysis with processing using Statistical Product and Service Solutions (SPSS) version 26 with data collection method through questionnaires to 70 employees of PT. Pegadaian. The results of this study indicate that there is an influence between Training (X1) and Employee Performance (Y) of 0.515 and has an effect of 51.5%. For the influence variable between Compensation (X2) and Employee Performance (Y) of 0.180 and has an effect of 18%. The influence variable between Work Discipline (X3) and Employee Performance (Y) is 0.153 and has an effect of 15.3%. The results showed that Training, Compensation and Work Discipline had a positive and significant effect on Employee Performance at PT. Pegadaian.